Strategi Pengembangan Minat dan Bakat Siswa di MIN 1 - NOORHAFIDZOH (Bahasa Indonesia, 2026)
ABSTRACT This study investigates the development of students’ interests and talents at MIN 1 Malang City through a qualitative research approach, emphasizing the strategies implemented by teachers and the educational environment in supporting students’ potential. Data were obtained through in-depth interviews with teachers, students, and parents to gain a comprehensive understanding of the practices, experiences, and challenges associated with nurturing students’ abilities. A qualitative method was employed to explore stakeholders’ perspectives regarding the processes of talent and interest development within the school setting. The findings indicate that the enhancement of students’ interests and talents is influenced by several factors, including the availability of extracurricular programs, the encouragement provided by teachers, parental participation, and the school’s commitment to individualized learning. However, the study also identifies challenges such as limited facilities, resource constraints, and time limitations that may hinder the optimal development of student potential. The research concludes that effective collaboration among teachers, parents, and school administrators plays a crucial role in fostering students’ interests and talents. Additionally, continuous monitoring, evaluation, and program improvement are necessary to ensure that educational initiatives remain responsive to students’ changing needs and developmental characteristics. Keywords: Student Development, Interests and Talents, Teacher Support, Parental Involvement, Qualitative Study..